HSV-2 infection of dendritic cells amplifies a highly susceptible HIV-1 cell target. - Elena Martinelli; Hugo Tharinger; Ines Frank; James Arthos; Michael Piatak; Jeffrey D Lifson; James Blanchard; Agegnehu Gettie; Melissa Robbiani (PLoS Pathogens)
Herpes simplex virus type 2 (HSV-2) increases the risk of HIV-1 infection and, although several reports describe the interaction between these two viruses, the exact mechanism for this increased susceptibility remains unclear. Dendritic cells (DCs) at the site of entry of HSV-2 and HIV-1 contribute to viral spread in the mucosa. Specialized DCs present in the gut-associated lymphoid tissues produce retinoic acid (RA), an important immunomodulator, able to influence HIV-1 replication and a key mediator of integrin α₄β₇ on lymphocytes. α₄β₇ can be engaged by HIV-1 on the cell-surface and CD4⁺ T cells expressing high levels of this integrin (α₄β₇ (high)) are particularly susceptible to HIV-1 infection. Herein we provide in-vivo data in macaques showing an increased percentage of α₄β₇ (high) CD4⁺ T cells in rectal mucosa, iliac lymph nodes and blood within 6 days of rectal exposure to live (n = 11), but not UV-treated (n = 8), HSV-2. We found that CD11c⁺ DCs are a major target of HSV-2 infection in in-vitro exposed PBMCs. We determined that immature monocyte-derived DCs (moDCs) express aldehyde dehydrogenase ALDH1A1, an enzyme essential for RA production, which increases upon HSV-2 infection. Moreover, HSV-2-infected moDCs significantly increase α₄β₇ expression on CD4⁺ T lymphocytes and HIV-1 infection in DC-T cell mixtures in a RA-dependent manner. Thus, we propose that HSV-2 modulates its microenviroment, influencing DC function, increasing RA production capability and amplifying a α₄β₇ (high)CD4⁺ T cells. These factors may play a role in increasing the susceptibility to HIV-1.